2018
DOI: 10.1186/s10194-018-0876-9
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of intrinsic brain activity in migraine with and without comorbid depression

Abstract: BackgroundMajor depressive disorder is a common comorbidity in migraineurs. Depression may affect the progression and prognosis of migraine. Few studies have examined the brain function in migraineurs that may cause this comorbidity. Here, we aimed to explore depression-related abnormalities in the intrinsic brain activity of interictal migraineurs with comorbid depression using resting-state functional magnetic resonance imaging.ResultsSignificant main effects of migraine and depression provided evidence that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(49 citation statements)
references
References 54 publications
1
46
0
2
Order By: Relevance
“…Cerebral cortex micro-architecture is different in patients with migraines and MDD compared to the patients who are suffering from a single disease [37][38]. In patients with both ailments, we also notice a discordant developmental track of the fusiform gyrus and detectable changes in the thalamus [37]. Changes are also evident in the control of pain and mood perceived by these comorbid individuals.…”
Section: Morphological Changes In Cerebral Cortex and Thalamusmentioning
confidence: 73%
See 1 more Smart Citation
“…Cerebral cortex micro-architecture is different in patients with migraines and MDD compared to the patients who are suffering from a single disease [37][38]. In patients with both ailments, we also notice a discordant developmental track of the fusiform gyrus and detectable changes in the thalamus [37]. Changes are also evident in the control of pain and mood perceived by these comorbid individuals.…”
Section: Morphological Changes In Cerebral Cortex and Thalamusmentioning
confidence: 73%
“…Generally, patients with depression have a two-fold chance of developing migraines [12]. There are differences in the brain tissue volumes among patients who encounter these two diseases [13]. Also, there is a 40-50% heritable association associated with migraine and major depressive disorder [14].…”
Section: Introductionmentioning
confidence: 99%
“…Abnormalities in this brain area can lead to depressive symptoms or migraine symptoms, the study found increased intrinsic brain activity in the left mPFC in people with depression. The mPFC, as the anterior node of the default mode network (DMN), was highly active at rest but inhibit activity during cognitive and emotional processing, migraineurs also exhibited increased intrinsic brain activity in the left mPFC . The DMN involves low‐frequency oscillations of about one fluctuation per second.…”
Section: Abnormal Brain Development and Brain Activitymentioning
confidence: 67%
“…Numerous studies of the structural or functional imaging of migraine have found a difference in the brain and abnormalities in specific cerebral areas. [17][18][19][20] There are discrepant developmental tracks of the fusiform gyrus, as well as the thalamus, in patients with migraine comorbid with depression. These trajectories are associated with transmission, recognition, control and memory of pain and mood.…”
Section: Ab Normal B R Ain De Velopment and B R Ain Ac Tivit Ymentioning
confidence: 99%
See 1 more Smart Citation